Will you still need me, will you still feed me when I'm 64? The Health Impact of Caregiving - P.L. de Zwart; P. Bakx; E.K.A. van Doorslaer (Tinbergen Institute, 2016)
Informal care may substitute for formal long-term care that is often publicly funded or subsidized. The costs of informal caregiving are borne by the caregiver and may consist of worse health outcomes and, if the caregiver has not retired, worse labor market outcomes. We estimate the impact of providing informal care to one's partner on the caregiver's health using data from the Survey of Health, Ageing and Retirement in Europe (SHARE). We exploit the panel structure of the data and use statistical matching to deal with selection bias and endogeneity. We find that in the short run caregiving has a substantial negative effect on the health of caregivers. These negative effects should be taken into account when comparing the costs and benefits of formal and informal care provision. These negative effects are potentially short-lived, however: we do not find any evidence that the health effects persist after 4 or 7 years.
Keywords: I12; I13; I19; 330; long term care; informal caregiving; health; SHARE